INTENSI MAHASISWA DALAM MENGEMBANGKAN EDUPRENEURSHIP: DITINJAU DARI PENDIDIKAN KEWIRAUSAHAAN DAN KREATIVITAS - Lestari, Amanda Tri; Dwiatmaja, Ahmad Zikri (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the influence of entrepreneurship education and creativity on students' intentions to develop edupreneurship at the Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar. The problem in this study stems from the high unemployment rate among college graduates, which indicates that the formation of entrepreneurial interest has not been optimal since college. This condition underlines the importance of strengthening the entrepreneurial spirit in the Faculty of Tarbiyah and Teacher Training. Therefore, research is needed that can provide empirical evidence regarding the role of entrepreneurship education and creativity in shaping students' entrepreneurial intentions. The approach used is quantitative with a survey method, and the data analysis technique uses Partial Least Square Structural Equation Modeling (PLS-SEM). The number of samples in this study was 75 respondents who were selected purposively. The research instrument was tested for validity and reliability through outer model and inner model analysis. The results of the study indicate that both entrepreneurship education and creativity have a positive and significant influence on students' intentions to develop edupreneurship. Creativity has a stronger influence than entrepreneurship education, with a path coefficient value of 0.669 and a significance of 0.000. Entrepreneurship education has a path coefficient value of 0.284 with a significance of 0.001. The conclusion of this study is that entrepreneurship education and creativity play an important role in fostering an entrepreneurial spirit among students. The implications of these results point to the need to strengthen the curriculum and learning that encourage innovation and entrepreneurial independence in the field of education